2017
DOI: 10.1080/15389588.2017.1320549
|View full text |Cite
|
Sign up to set email alerts
|

A spectral power analysis of driving behavior changes during the transition from nondistraction to distraction

Abstract: This study suggests that driver state detection needs to consider the behavior changes during the prestarting periods, instead of only focusing on periods with physical presence of distraction, such as cell phone use. Lateral control measures can be a better indicator of distraction detection than longitudinal controls. In addition, frequency domain analyses proved to be a more robust and consistent method in assessing driving performance compared to time domain analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The measures used in this study are time domain measures. Wang, Bao, Du, Ye, and Sayer (2017) used fast Fourier transform (FFT) to extract the frequency domain measures and showed that the results based on the frequency measures were more robust and consistent than that based on the time measures. However, Wang et al (2017) noted that FFT may not be a good method to interpret the dynamic changes (e.g., lane changes) because FFT generally assumes a steady-state process.…”
Section: Discussionmentioning
confidence: 99%
“…The measures used in this study are time domain measures. Wang, Bao, Du, Ye, and Sayer (2017) used fast Fourier transform (FFT) to extract the frequency domain measures and showed that the results based on the frequency measures were more robust and consistent than that based on the time measures. However, Wang et al (2017) noted that FFT may not be a good method to interpret the dynamic changes (e.g., lane changes) because FFT generally assumes a steady-state process.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have analysed adaptations in driver behaviour capturing the impact of several explanatory factors and interdependencies between repeated observations over time for the same subject. For this purpose, recent studies have proposed linear mixed-effects models for repeated measures, which can accommodate both fixed and random effects capturing complex error structures (Peng, Boyle, and Lee 2014;Peng and Boyle 2015;Oviedo-Trespalacios et al 2017;Wang et al 2017;Geden, Staicu, and Feng 2018;Saad, Abdel-Aty, and Lee 2018;Albert 2019). Linear mixed-effects models allow to define explicitly a hierarchical structure (e.g.…”
Section: Statistical Analysis Methods For Adaptations In Driver Behavmentioning
confidence: 99%
“…Appropriate identification of risk factors affecting traffic accidents is necessary. From the existing research, driver attributes [53], weather conditions [54], traffic characteristics [55], driving behavior [56], temporal-spatial distribution [57] and vehicle types [58] can all influence the possibility of a traffic accident. We established the risk factor system based on the literature plus two newly added risk factors, i.e., weaving ratio and accident location.…”
Section: Methodsmentioning
confidence: 99%